2019
DOI: 10.1136/bcr-2019-230055
|View full text |Cite
|
Sign up to set email alerts
|

Dentures discovered in larynx 8 days after general anaesthetic

Abstract: An active 72-year-old man presented to the accident and emergency department (A&E) with odynophagia, dysphagia and haemoptysis 6 days after a minor operation and was discharged after treatment for an aspiration pneumonia. He presented to A&E 2 days later with worsening symptoms and was found to have dentures lodged in his larynx which were then removed in theatre. For 6 weeks after removal, he had periodic episodes of frank haemoptysis requiring multiple blood transfusions and, after extensive investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…After discovering and removing the dentures, he developed aspiration pneumonia and hemoptysis due to granulation tissue formation. This study concluded that any dental prosthesis should be documented before and after any procedure, and the perioperative strategy should be communicated to all members of the operating room [ 6 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…After discovering and removing the dentures, he developed aspiration pneumonia and hemoptysis due to granulation tissue formation. This study concluded that any dental prosthesis should be documented before and after any procedure, and the perioperative strategy should be communicated to all members of the operating room [ 6 ].…”
Section: Reviewmentioning
confidence: 99%
“…Aspiration pneumonia, halitosis, infective endocarditis, septic meningitis, and other complications can result from biofilm formation. In addition, accidental aspiration and ingestion of dentures are also more common in the elderly; potential risk factors include alcoholic intoxication, advancing dementia, stroke, and epilepsy [ 6 ]. Necrosis, perforation, ulceration, fistula formation, penetration of neighboring organs, bleeding, and obstruction are risks associated with ingesting dentures [ 6 - 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patient gender was specified in all but one case report and in all case series, and about 8 out of every 10 patients were male. [3][4][5][6][7][8][9][10][11] Patient gender was specified for patients in all but one of the retrospective reviews that were analyzed; nearly 7 out of 10 patients in these reviews were male. 41-45 While it seems clear that men are more likely to experience a denture impaction event, the reason for this is unclear.…”
Section: Gender and Age Distributionmentioning
confidence: 99%
“…Several patients were unaware that they had swallowed a denture, so the healthcare provider lacked that information when attempting to identify the etiology of the patient's symptoms. 3,9,29,33,36 Notably, the patient's symptoms in two cases were initially attributed to a suspected malignancy in the sigmoid colon, but surgical resection led to the identification of an impacted partial plate in both cases. 9,16…”
Section: Delayed Diagnosis Of Denture Impactionmentioning
confidence: 99%
See 1 more Smart Citation